2012
DOI: 10.1002/ase.1295
|View full text |Cite
|
Sign up to set email alerts
|

Design and validation of a novel learning tool, the “Anato‐Rug,” for teaching equine topographical anatomy

Abstract: Recognition of anatomical landmarks in live animals (and humans) is key for clinical practice, but students often find it difficult to translate knowledge from dissection-based anatomy onto the live animal and struggle to acquire this vital skill. The purpose of this study was to create and evaluate the use of an equine anatomy rug ("Anato-Rug") depicting topographical anatomy and key areas of lung, heart, and gastrointestinal auscultation, which could be used together with a live horse to aid learning of "liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 46 publications
(91 reference statements)
0
9
2
Order By: Relevance
“…The model was however at least as beneficial as the textbook, since student test scores post‐learning exercise were similar regardless of study method. The lack of difference between Experimental and Control groups falls in contrast to a similar study of comparable design (Braid et al, ) which found 16% higher performance in students who had used a model horse wearing an anatomical rug depicting anatomical structures compared to those studying using textbooks alone. On initial inspection the learning exercises in the two studies appear similar–using color and simple illustration on a life‐sized model to aid learning.…”
Section: Discussioncontrasting
confidence: 86%
See 2 more Smart Citations
“…The model was however at least as beneficial as the textbook, since student test scores post‐learning exercise were similar regardless of study method. The lack of difference between Experimental and Control groups falls in contrast to a similar study of comparable design (Braid et al, ) which found 16% higher performance in students who had used a model horse wearing an anatomical rug depicting anatomical structures compared to those studying using textbooks alone. On initial inspection the learning exercises in the two studies appear similar–using color and simple illustration on a life‐sized model to aid learning.…”
Section: Discussioncontrasting
confidence: 86%
“…On initial inspection the learning exercises in the two studies appear similar–using color and simple illustration on a life‐sized model to aid learning. However, a key difference is that the “Anatorug” (Braid et al, ) was interactive, allowing students to stick labels to the rug. This simple addition of an “active” component to the resource may account for the apparent greater efficacy of the “Anatorug” over the painted model in the current study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based upon our collective experience with various types of veterinary student rectal palpation training, it is clear that many of the palpable structures within the abdomen (namely the spleen, nephrosplenic ligament or space, small intestinal mesenteric root, cecum or ventral cecal band, small and large intestine, and reproductive structures) are often difficult for students to identify. Presumably this results from a lack of understanding of the location and characteristic tactile sense of the structure and difficulty on the students' part making the transition from dissection‐based anatomy classes to identification via rectal examination . It is likely that the improved learning outcome achieved with laparoscopic‐guidance during this study results directly from the immediate, combined visual and tactile sensory feedback that this technology enables for students, and the superior guidance and teaching opportunities laparoscopy grants instructors.…”
Section: Discussionmentioning
confidence: 98%
“…Notwithstanding, the application of novel techniques for teaching veterinary anatomy in live animals is still rare [2].…”
Section: Introductionmentioning
confidence: 99%